2010
DOI: 10.1111/j.1553-2712.2009.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Comes Back? Characteristics and Predictors of Return to Emergency Department Services for Pediatric Mental Health Care

Abstract: Objectives: The objective of this study was to investigate predictors of emergency department (ED) return visits for pediatric mental health care. The authors hypothesized that through the identification of clinical and health system variables that predict return ED visits, which children and adolescents would benefit from targeted interventions for persistent mental health needs could be determined.Methods: Data on 16,154 presentations by 12,589 pediatric patients (£17 years old) were examined from 2002 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
89
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 45 publications
5
89
3
1
Order By: Relevance
“…We decided a priori to include age, sex, race, ethnicity, region, urban status, and year in the model, as they have been previously demonstrated to be associated with differences in both ED and psychiatric care. 3,6,7,11,12,16,[19][20][21][22][23][24] For the length of stay (LOS) analysis as our secondary outcome, we tested for trend the median visit length. Median LOS is used in place of the mean LOS as values were not normally distributed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided a priori to include age, sex, race, ethnicity, region, urban status, and year in the model, as they have been previously demonstrated to be associated with differences in both ED and psychiatric care. 3,6,7,11,12,16,[19][20][21][22][23][24] For the length of stay (LOS) analysis as our secondary outcome, we tested for trend the median visit length. Median LOS is used in place of the mean LOS as values were not normally distributed.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Outpatient access to psychiatric care for children may be limited, especially in certain at-risk socioeconomic groups. 6,[11][12][13][14] While the PECARN study and several Canadian studies have suggested that socioeconomic factors may be associated with high odds of ED psychiatric visits, 3,12,[15][16][17] no study has evaluated these factors using nationally representative United States data. The specific focus of this study was on sociodemographic factors and their effect on odds of ED visits.…”
mentioning
confidence: 99%
“…7,13 Repeat presentations represent a large proportion of PED MH presentations with estimates ranging from 12% to 36%. [14][15][16] This may be the result of a lack of availability or difficulty accessing MH services that effectively meet this patient population's needs. 14,17 Findings on predictors of repeat PED for MH issues are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…7 More recent Alberta-based research has suggested that mood-based crises are among the most frequent reasons for pediatric mental health emergency department (ED) visits. 8 A related study reported adolescents aged 13 to 17 were 1.5 times more likely to return for subsequent ED care compared to 6 to 12 year olds, 9 and that within 72 hours of ED discharge, 6% of children and adolescents diagnosed with a mood disorder will return for further acute care. 9 Combined, this body of Canadian literature suggests that Canadian adolescents are engaging a pattern of acute mental health services use with little to no receipt of community-based or primary care health care.…”
mentioning
confidence: 99%
“…8 A related study reported adolescents aged 13 to 17 were 1.5 times more likely to return for subsequent ED care compared to 6 to 12 year olds, 9 and that within 72 hours of ED discharge, 6% of children and adolescents diagnosed with a mood disorder will return for further acute care. 9 Combined, this body of Canadian literature suggests that Canadian adolescents are engaging a pattern of acute mental health services use with little to no receipt of community-based or primary care health care. Large, national efforts to improve access to and receipt of mental health services in childhood and adolescence are ongoing (e.g., Mental Health Commission of Canada surveillance techniques in Canada's health databases as a practical and cost-effective strategy to reveal patterns of mental health resource use and inform health resource planning.…”
mentioning
confidence: 99%